Intraoperative slow-release dexamethasone intravitreal implant (Ozurdex) in epiretinal membrane peeling surgery: a prospective randomized controlled trial - Li, Siying; Zeng, Qiaozhu; Zhu, Li; Liu, Wenbo; Li, Yujing; Li, Jiarui; Li, Xiaoxin; Zhao, Mingwei; Qu, Jinfeng (Frontiers in Pharmacology, 2023)
Abstract Purpose To determine the efficacy of the dexamethasone (DEX) intravitreal implant for the regression of macular edema and the improvement of best-corrected visual acuity (BCVA) after removal of idiopathic epiretinal membrane (ERM). Methods This prospective randomized controlled trial recruited 81 patients with idiopathic ERM. These patients all underwent 25-gauge (G) pars plana vitrectomy (PPV) combined with ERM and inner limiting membrane (ILM) peeling surgery. Among them, 41 eyes in DEX group received additional DEX implant and 40 in non-DEX group had not. Outcomes including central retinal thickness (CRT)， BCVA and intraocular pressure (IOP) were measured at 1 and 3 months after surgery. Results DEX group had thinner CRT than that in non-DEX group at 1-month postoperatively (P<0.05), but did not differ significantly at the 1-week and 3-month follow-up visits (P=0.109 and P=0.417, respectively). There were no statistical differences with respect to BCVA (P=0.499, 0.309, 0.246 and 0.517, respectively) as well as IOP (P=0.556, 0.639, 0.741 and 0.517, respectively) between the two groups at each point of follow-up visit. Conclusion DEX accelerated the reduction of CRT at 1 month after surgery. However, no evidence of further anatomical (CRT) or functional (BCVA) benefit by DEX was observed at 3 months.